EP971 Survival impact of wide resection of the pelvic peritoneum in patients with epithelial ovarian cancer. (1st November 2019) - Sagara, A; Motohara, T; Iwagoi, Y; Saito, F; Takaishi, K; Miyahara, Y; Sakaguchi, I; Honda, R; Tashiro, H; Katabuchi, H
Abstract : Introduction/Background: The present study was designed to evaluate the effect of the peritoneal stripping method termed 'wide resection of the pelvic peritoneum (WRPP)' on eliminating disseminated tumors in the pelvic peritoneum and whether there is any survival benefit for patients with epithelial ovarian cancer. Methodology: From January 2000 to December 2018, 460 patients with epithelial ovarian cancer were treated surgically at Kumamoto University Hospital. The clinical and surgical records of these patients were reviewed retrospectively, and 225 patients with ovarian cancer who underwent standard definitive surgery were included in this study. Eligible patients with ovarian cancer were divided into 3 groups according to surgical approach. Patients in the standard surgery group underwent cytoreduction with standard surgical techniques (n=65). The WRPP group consisted of patients who underwent standard surgery plus WRPP (n=125). The RS group included patients who required standard surgery plus rectosigmoidectomy (RS) (n=35). The primary outcome measure was overall survival. The secondary endpoint was recurrence-free survival. Results: Overall survival was significantly longer in the WRPP group than in the standard surgery group for patients with stage III–IV disease (P<0.05). The WRPP group was less prone to recurrence than the standard surgery group (P=0.70). In addition, the intrapelvic recurrence rate differed significantly between the standard surgery and WRPP groups (38.2% vs. 23.8%, P<0.01). Conclusion: WRPP is an effective procedure that should be a part of the skill set of any gynecological surgeon performing surgical cytoreduction in patients with advanced ovarian cancer. The addition of this surgical technique has the potential to improve patient outcomes. Disclosure: Nothing to disclose.